Evaluation of the Multidisciplinary Assistance provided in a Public Neonatal Care Unit from mothers` perception - Mariana Fanstone Ferraresi; Alessandra da Rocha Arrais
Abstract Objectives: this study aimed to investigate the evaluation of mothers about the care provided by the multidisciplinary team in a Public Neonatal Care Unit located in the Federal District/Brazil. Methods: this is a descriptive, quantitative and cross-sectional study. The sample consisted of 57 mothers and data were collected from April to September 2015. The instrument used for data collection was a questionnaire with questions distributed in three main domains, such as accessibility and accommodation; communication and relationship with the team and assistance received. Results: the result showed an association of mothers' satisfaction with the variables "income" and "length of hospital stay", and demonstrated that the majority of the mothers evaluated the unit positively. However, it was highlighted the need to improve communication between neonatal staff and mothers, and to implement a more flexible visiting policy in order to allow the presence of other family members in the mentioned Unit more frequently. Conclusions: data obtained from this research may contribute to improve the quality of care in the NICUs, in view of the importance of evaluation of assistance so that better care to mothers is available.